OPTIMIZATION OF MARKETING USING SOCIAL MEDIA AND ADVERTISING MEDIA IN INCREASING SALES AT THE UNITYLIGHT ONLINE STORE IN MAKASSAR CITY - RAHMAT DINUL PAQI; AGUS SYAM, NUR HALIM, MUHAMMAD JUFRI, SUMIATI TAHIR (Jurnal Ekonomi dan Bisnis, 2026)
Digital marketing through social media and advertising media has become one of the important strategies in facing the challenge of low sales volume in the current digital era. Amid the increasingly fierce online business competition, optimal utilization of social media becomes the key to reaching consumers widely and boosting sales. This research aims to identify the optimization strategies for marketing using social media and media advertising to increase sales at the Unitylight Online Store in Makassar City. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The strategies implemented include creating feed and reels content, adding Call To Action (CTA) links, using automated messages, compiling product catalogs, and utilizing Instagram Ads. Data analysis employs the AIDA model (Attention, Interest, Desire, Action) approach to illustrate an effective marketing communication flow. The research results show that the implemented digital marketing strategy has impacted the increase in sales volume, profit acquisition, and supported the growth of Unitylight Online Store. These findings contribute to MSME actors in utilizing digital technology in a more targeted and strategic manner.